The heterogeneous effects of entry on prices - Kai Fischer; Simon Martin; Philipp Schmidt-Dengler (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
We study the effect of entry on the price distribution in the German retail gasoline market. Exploiting more than 700 entries over five years in an event study design, we find that entry causes a persistent first-order stochastic shift in the price distribution. Prices at the top of the distribution change moderately only, but prices at the left tail decrease by up to 12% of stations' gross margins. Consumers with easy access to information on prices gain the most from entry. The reduction in transaction prices is 32-44% stronger for fully informed consumers than for uninformed consumers.
Keywords: D22; L11; D83; L81; R32; 330; Entry; information frictions; price distribution; (unconditional) quantile treatment effects